Education in Times of War: Narrative Accounts of Displacement and Continuity in Ukrainian Schools - Dmytro Ivanov; Natalia Holub; Oleg Solovey (Yayasan Adra Karima Hubbi, 2025)
Background. The ongoing conflict in Ukraine has disrupted the educational landscape, displacing students, teachers, and families while threatening the continuity of learning across the country. Amidst the instability of war, Ukrainian schools have demonstrated remarkable resilience, adapting pedagogical approaches and redefining the meaning of education under crisis. Purpose. This study explores how educators and students experience and respond to displacement, loss, and continuity in war-affected regions of Ukraine. Using a qualitative narrative methodology. Method. the research draws on in-depth interviews with 18 teachers and 12 students from internally displaced and frontline communities. Participants shared stories of interrupted schooling, digital adaptation, emotional trauma, and communal support. Results. The findings reveal that while infrastructural damage and psychological stress hinder formal instruction, educators and learners have found ways to preserve educational values through flexible delivery methods, psychosocial initiatives, and community-driven learning spaces. Schools emerged not only as academic institutions but as emotional anchors and symbols of national identity. Conclusion. The study highlights the importance of narrative as a tool for documenting lived experiences and advocating for education continuity in conflict zones.